Neonatal hemochromatosis attributed to gestational alloimmune liver disease treated with intravenous immunoglobulin and exchange transfusion therapy: an evidence-based case report - Adhi Teguh Perma Iskandar; Vini Jamarin; Kamajaya Mulyana (Indonesian Pediatric Society, 2021)
Neonatal hemochromatosis (NH) is a rare fatal liver disease accompanied by hepatic and extrahepatic iron overload.1-3 Gestational alloimmune liver disease (GALD) is a materno-fetal alloimmune disorder and leading cause of NH.2,4,5 This condition allows an interplay between the maternal adaptive immune system and the fetus, resulting in an allograft to the mother. The mother becomes sensitized to an alloantigen expressed by the fetus and forms specific reactive antibodies. Immunoglobulin G (IgG) is transported through the placenta and attacks the fetal hepatocytes, resulting in severe loss of hepatocytes and fetal iron overload.3,6 Liver transplantation has been the only definitive treatment for NH for many years, with a survival rate of Â±35%. Conventional therapy containing antioxidants and chelation agents reportedly have very poor success, with survival rate of only 10-20%. A new treatment paradigm involving intravenous immunoglobulin (IVIG) and exchange transfusion (ET) therapy has shown significant success in survival rate in NH, decreasing the need for liver transplantation.3,7,8 Here we present a case of NH caused by GALD and treated successfully with a combination of IVIG therapy and ET. We also aimed to evaluate the efficacy of IVIG and ET therapy for NH.